2016
DOI: 10.1152/jn.00196.2016
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and hypercapnia inhibit hypothalamic orexin neurons in rats

Abstract: Evidence of impaired function of orexin neurons has been found in individuals with cardiorespiratory disorders, such as obstructive sleep apnea (OSA) and sudden infant death syndrome (SIDS), but the mechanisms responsible are unknown. Individuals with OSA and SIDS experience repetitive breathing cessations and/or rebreathing of expired air, resulting in hypoxia/hypercapnia (H/H). In this study, we examined the responses of fluorescently identified rat orexin neurons in the lateral hypothalamus to acute H/H to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…This phenomenon explains the classic clinical manifestation, described in 1999 by the senior author ( 4 ). It seems that a defect interaction of neurons might play a principal role to be prone to the TCR ( 36 ) as it was already suggested in case of the SIDS ( 37 ).…”
Section: Resultsmentioning
confidence: 82%
“…This phenomenon explains the classic clinical manifestation, described in 1999 by the senior author ( 4 ). It seems that a defect interaction of neurons might play a principal role to be prone to the TCR ( 36 ) as it was already suggested in case of the SIDS ( 37 ).…”
Section: Resultsmentioning
confidence: 82%
“…The generation of these transgenic animals in which Cre recombinase and green fluorescent protein are exclusively expressed in hypothalamic orexin neurons has been described previously (Dergacheva et al, 2016). Rats were housed in the George Washington University animal care facility.…”
Section: Methodsmentioning
confidence: 99%
“…RTIOX‐276 and TCS‐OX2‐29 are selective antagonists for orexin‐1 and orexin‐2 receptors, respectively. Recent studies have shown that hypoxia and hypercapnia inhibit orexin neurons through conformational changes at the level of the postsynaptic membrane . Hypoxia and hypercapnia‐induced changes cause abnormal membrane depolarization resulting in neural depression and failure to send electrical impulses to effector cells.…”
Section: Inhibitors Of Orexin Expression and Activitymentioning
confidence: 99%